Migraine Associated Symptom Prevalence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
A review of associated symptoms of migraine determined by telephone survey of 500 self-reported migraine sufferers is reported from Temple University School of Medicine and the Comprehensive Headache Center, Germantown Hospital, Philadelphia, PA.